Advocacy Coalition Framework of Ultra Micro Loan Policymaking in Indonesia - Nining I Soesilo (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Advocating the Ultra Micro-lending concept of Indonesia's Ministry of Finance in 2017 was a tumultuous nine-year process. The present paper aims to examine the Ultra Micro-lending (UMi) program conducted by the Ministry of Finance of Republic of Indonesia using Advocacy Coalition Framework. This paper showed that Advocacy Coalition Framework could moderate the interest groups' disagreementÂ through seven steps as follows. First, relatively stable parameters of poverty need alleviation using better financial access with empowerment. Second, the external system is inspired by Grameen Bank as the winner of the Nobel Peace Prize. Third, removing constraints and resources of subsystem actors from the internal Ministry of Finance and the Parliaments. Fourth, creating consensus for getting the Ministry of Bureaucratic Reform's permit. Fifth, policy subsystem that coalesces the need of market-rate and subsidized rate to caterÂ to 46.7 million grassroots entrepreneurs as a 'win-win' arrangement to complement the bank-based People's Business Credit (KUR).Â Sixth, policy outputs as the legal product of the UMi with a 7 Trillion State budget. Seventh, policy impact's measurement after one year piloting before UMi's scaling up. This paper has a significant contribution to enhancing the efficacy of UMi program, and as a continuous effort to ensure the economic development of the country.